2015
DOI: 10.1186/s40880-015-0043-5
|View full text |Cite
|
Sign up to set email alerts
|

Carcinogenic effects of circadian disruption: an epigenetic viewpoint

Abstract: Circadian rhythms refer to the endogenous rhythms that are generated to synchronize physiology and behavior with 24-h environmental cues. These rhythms are regulated by both external cues and molecular clock mechanisms in almost all cells. Disruption of circadian rhythms, which is called circadian disruption, affects many biological processes within the body and results in different long-term diseases, including cancer. Circadian regulatory pathways result in rhythmic epigenetic modifications and the formation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 63 publications
(93 reference statements)
0
15
0
Order By: Relevance
“…Most epidemiological studies assessing the possible association between shiftwork and cancer have focused on breast cancer, and the evidence on other tumour sites remains scarce 14 15. While it has been hypothesised that circadian disruption may be implicated in the onset of colorectal cancer,16 only four studies have investigated this association 17–20. These studies have had inconsistent results and been criticised for their methodological limitations 21…”
Section: Introductionmentioning
confidence: 99%
“…Most epidemiological studies assessing the possible association between shiftwork and cancer have focused on breast cancer, and the evidence on other tumour sites remains scarce 14 15. While it has been hypothesised that circadian disruption may be implicated in the onset of colorectal cancer,16 only four studies have investigated this association 17–20. These studies have had inconsistent results and been criticised for their methodological limitations 21…”
Section: Introductionmentioning
confidence: 99%
“…Circadian rhythms are observed in most biochemical messengers, including hormones and cytokines. Growing evidence has shown that the disruption of the circadian control often accelerates the development of various chronic diseases [1]. The role of inflammatory cytokines in the progression of chronic diseases such as cancer, diabetes and obesity is crucial.…”
Section: Introductionmentioning
confidence: 99%
“… 15 In addition, aberrant epigenetic modifications (eg, hypermethylation) due to circadian disruption can lead to a variety of cancers even in the absence of circadian gene mutations. 28 Koike et al in a study on core circadian clock in mammals showed that almost 22% of the circadian regulation of messenger RNA (mRNA) transcripts is exerted at the transcriptional level and the rest is posttranscriptionally regulated. Thus, different posttranscriptional regulations including various epigenetic modifications (eg, H3K9ac, H3K27ac, and H3K4me3) play a significant role in the circadian cycling of mRNA transcripts.…”
Section: Introductionmentioning
confidence: 99%